Potential of Harum Manis Mango (Mangifera Indica L.) Seed Extract for Nosocomial Infections - Wahdaniar; Imran Pashar; Miladiarsi; Ade Irma (Journal of Public Health Sciences, 2023)
Nosocomial infections occur in hospitals and attack patients who are in the recovery process and have low immunity. The emergence of nosocomial conditions in the hospital environment is caused by bacteria and moist objects or materials, especially in the operating room and even the treatment room for children and babies. One type of bacteria that causes the infection is Pseudomonas aeruginosa. P. aeruginosa has been recognized as an irreversible problem in hospitals due to resistance to 3 antibiotic classes. The content of sweet mango seeds has a high phytochemical content in the form of steroid compounds, terpenoids, flavonoids, alkaloids, phenolics, tannins and saponins. This study aimed to determine the potential of sweet mango seed extract against nosocomial infections. The research method is quantitative experimental, using ethanol extract of sweet fragrant mango seeds with well diffusion and dilution tests (MIC and MBC). The results of the antibacterial activity test measured the inhibition zone formed and tested MIC and MBC. MIC value of sweet fragrant mango seed extract showed at 1.56 mg/mL and 0.78, and at MBC value of 25 mg/mL and 50 mg/mL. The results of sweet fragrant mango seed extract have the potential to be developed as an antibacterial agent, especially against nosocomial infections.